Bioaccumulation of Pb(II) From Aqueous Solutions by Bacillus cereus M1 16 - L. Ray; S. Paul; D. Bera; P. Chattopadhyay (Journal of Hazardous Substance Research, 2006)
Because of the severity of heavy metal contamination and potential adverse health impact on the public, tremendous efforts have been made to purify waters containing toxic metal ions. Biosorption is presented as an alternative to traditional physicochemical means for removing toxic metals from groundwaters and wastewaters. Removal of lead from solution was studied using growing cells and washed cells of Bacillus cereus M116. The removal of Pb(II) ions with growing cells was maximum (85%) when initial lead concentration was 50 mg/L. Other process conditions were optimized. These were volume of medium: 40 ml in a 250-ml Erlenmeyer flask, temperature: 30° C, pH: 6.0, fermentation time: 30 hours, and inoculum concentration (24-hour cell growth): 4%. Biosorption of Pb(II) on washed biomass of the selected strain was investigated in batch mode and optimum conditions were determined. The uptake of metal was very fast, and equilibrium was attained within 30 minutes. It was found that the overall adsorption process was best described by pseudo second-order kinetics. Both Langmuir and Freundlich isotherms were tested, and it was found that the latter had a better fit with the data. The adsorption continuously increased in the pH range of 3.6 – 6.0, beyond which the adsorption could not be carried out due to precipitation of metal. The highest value of lead uptake was 96%, with 1.8 g/L washed biomass (dry basis) at 20°C and 92% at 30°C.
Keywords: lead biosorption; Bacillus sp.; adsorption; isotherm